Sampling errors of quantile estimations from finite samples of data - Roy, Philippe; Laprise, R.; Gachon, P. (2016)
Empirical relationships are derived for the expected sampling error of quantile estimations using Monte Carlo experiments for two frequency distributions frequently encountered in climate sciences. The relationships found are expressed as a scaling factor times the standard error of the mean; these give a quick tool to estimate the uncertainty of quantiles for a given finite sample size.
Keywords: Gachon_Philippe